Digital product development that scales: Cases from the CGIAR - Talsma, Tiffany; Nguyen, Thuy Thanh; Ouedraogo, Mathieu; Jimenez, Daniel; Kagabo, Desire (2025)
Digital innovation is central to CGIAR’s mission to transform agri-food systems, yet many digital products struggle to transition from promising prototypes to scalable, self-sustaining solutions. This report, Digital Product Development that Scales: Cases from the CGIAR, examines why this gap persists and what can be done to close it. Drawing on in-depth interviews and structured assessments of eight CGIAR digital products—supplemented by comparative insights from private-sector platforms—the study evaluates performance across six stages of the digital product lifecycle, from discovery to scale. The analysis reveals that CGIAR products consistently perform strongly in early stages of ideation and definition, reflecting institutional strengths in research-driven innovation and problem identification. However, performance declines markedly in later stages—particularly minimum viable product (MVP) development and scaling—where market readiness, sustained funding, user-centered design, and institutional support become critical. Commissioned products, backed by clear mandates, stable funding, and early stakeholder engagement, significantly outperform non-commissioned, internally initiated products, which often rely on individual effort and lack formal pathways to sustainability. The report highlights systemic challenges—including grant dependency, limited scalability planning, and weak feedback loops—but also identifies clear opportunities for improvement. Evidence from both CGIAR case studies and private-sector comparators underscores the importance of agile development practices, consistent user engagement, and a distinct “stabilization” phase focused on technical reliability, financial viability, and institutional embedding. The findings point to a strategic imperative for CGIAR to complement its research excellence with lean, human-centered product development approaches. By strengthening support mechanisms—particularly for non-commissioned innovations—and fostering cross-sector learning, CGIAR can significantly enhance the scalability, sustainability, and long-term impact of its digital product portfolio.